2017
DOI: 10.1016/j.molliq.2017.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductances of aqueous electrolytes at high temperatures: Limiting mobilities of several ions including the proton and HCl dissociation constant

Abstract: The empirical equation of R.H.Wood for limiting equivalent NaCl conductance and a set of equations for a proton and other ions in the aqueous solutions HCl, LiCl, NaCl, KCl, Li 2 SO4, K 2 SO4 and mixtures H 2 SO4-Na 2 SO4-H 2 O are revisited and compared with equations of other authors. The Wood equation is unique in an accurate description of the region close to the critical point of water. In this region the decrease in limiting ion mobilities correlate with the increase in water compressibility. In a remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…A regression fit yielded 1 = 2550.14 ± 99.57, 2 = −505.10 ± 117.76, 3 = −429,437 ± 22,442 (R 2 = 0.97). Figure 5 compares measured and predicted values, including also some data from Ho et al (2001) and Balashov et al (2017) measured at relatively low pressures up to about 30 MPa. Note that in contrast to the regression equation used by Sinmyo and Keppler (2017) for the limiting molar conductivity of NaCl, Eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A regression fit yielded 1 = 2550.14 ± 99.57, 2 = −505.10 ± 117.76, 3 = −429,437 ± 22,442 (R 2 = 0.97). Figure 5 compares measured and predicted values, including also some data from Ho et al (2001) and Balashov et al (2017) measured at relatively low pressures up to about 30 MPa. Note that in contrast to the regression equation used by Sinmyo and Keppler (2017) for the limiting molar conductivity of NaCl, Eq.…”
Section: Discussionmentioning
confidence: 99%
“…They were fitted to a model Λ 0 = 1 + 2 + 3 ∕T with 1 = 2,550.14 ± 99.57, 2 = −505.10 ± 117.76, 3 = −429,437 ± 22,442; R 2 = 0.97. For comparison, data from Ho et al (2001;blue circles) and Balashov et al (2017;green circles) are also shown for fluid densities >0.5 g/ cm 3 . For lower fluid densities, the uncertainties in the measured values become very large Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arrhenius energy term, [E η − E λ ] = c + d ln ρ w , was taken from the expression for the standard molar internal energy of reaction from the "density" model, 7,67,68 which describes the solvent compressibility effects on chemical equilibria at elevated temperatures and pressures. The equation is similar to Balashov's model 6 for NaCl discussed below but does not include the second structural term expressed by "α 10 ln ρ w + α 1 κ κ + α 2 ρ ρ w ." Balashov and Wood Sodium Chloride Based Correlation.…”
Section: High Temperature Models For K + and CL −mentioning
confidence: 99%
“…Balashov and Wood Sodium Chloride Based Correlation. 6 The most recent approach has been reported by Balashov et al 6 and involved calculation of the product of Λ°N aCl η w via a logarithmic relationship of this product to temperature, solvent density, compressibility values, and six parameters obtained by regression.…”
Section: High Temperature Models For K + and CL −mentioning
confidence: 99%